Tajikistan - Feasibility Study for Results-Based Financing (RBF) In the Health Sector - World Bank (World Bank, 2012)
The purpose of this study is to examine the feasibility of introducing Results-Based Financing (RBF) in Tajikistan's health sector. Several countries have experience with RBF in low-income settings, and lessons learned can be interesting for Tajikistan. Technically, RBF is a retrospective provider payment that can be designed to reimburse providers for contractually defined services and specific compliance targets, including for efficiency and quality targets. In Tajikistan RBF will be linked to ongoing provider payment reforms. Therefore, the chapter also provides a brief overview on provider payment mechanisms and experience with provider payment reforms and treatment patterns from middle- and higher-income countries. The objective of this feasibility study is to propose a sustainable RBF pilot program for two oblasts (Khatlon and Sughd), to cost-effectively improve maternal and child health (MCH) outcomes. The study aims to inform the health sector strategy and help the Government and partners to effectively design and use RBF mechanisms at three potential levels. First, the fiscal transfer from the central government to oblasts (regions) and rayons (districts) could be adjusted to include a bonus payment based on specific results achieved. Second, the provider payment method from oblast health fund pools to hospitals and outpatient facilities could reward providers based on results indicators. Third, a performance payment could be added to salaries paid to staff working in health facilities. It is expected that such a three-pronged approach could reinforce the financial incentive set through RBF to staff working in the administration and provision of care. If the staff responds to these incentives, then this could lead to better management in oblast and rayons, improved availability of financial resources and medical material in health facilities, and better treatment of patients. Combined, these behavioral changes will ultimately lead to better health results, including improved quality of care and in the longer-run improved health status.